Pengaruh Penggunaan Media Pembelajaran Kahoot Terhadap Hasil Belajar Dasar-Dasar Akuntansi Siswa Kelas X Jurusan Akuntansi dan Keuangan Lembaga di SMK Negeri 1 Singaraja - Tarigan, Maissy Christiani; Santi, Ni Wayan Ayu (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of using Kahoot learning media on the learning outcomes of accounting basics significantly. This research design is a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The population in this study is 106 class X students majoring in Accounting and Financial Institutions in 2023/2024, with a total sample of 70 students divided into 2 groups, namely 35 experimental class students and 35 control class students. The sampling technique uses a simple random sampling technique. Data collection techniques used in the study used study test results, interviews, and documents. The data were analyzed by paired sample t-test. The results of this study show that the use of Kahoot learning media has a significant effect on the learning outcomes of the basics of accounting for grade X students majoring in Accounting and Financial Institutions at SMK Negeri 1 Singaraja.